Identifikasi Air Tanah Berbasis Model Struktur Geologi dengan Metode Geolistrik - Darmawan, Azhar Adi; Garside, Annisa Kesy; Setyono, Ernawan; Saleh, Chairil (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The aim of this research is to identify groundwater based on geological structure models using geoelectric methods in Purwosekar Village, Tajinan District, Malang Regency. The technology used in this research is the geoelectric resistivity method which helps identify rock structures and deep groundwater potential. The findings showed that the recommended drilling point was with a discharge of around 5.6 L/sec. At this location there is rock lithology consisting of topsoil, tuff, sandy tuff and lava.